Post-Pandemic Concert: What Would Have Changed For Orchestral Performance in Indonesia - Matias, Ferry (PROMUSIKA, 2021)
The pre-pandemic era has been established the settled living ecosystem for orchestral musician in Indonesia, nevertheless, due to the government's policy to combat the virus since March 2020 which is applying the social restriction on a large scale, those within creative sectors have totally ceased their activities. As time goes by, online-virtual-concert has enlivened musical creating and performing. It spread globally and was responded as an opportunity by the state representation so did by the private sectors who have developed the platforms to accommodate the musician rights as brought by UNESCO discourses, one of formulated as follows “musicians can express themselves through music and get fair remuneration from it.” The developed platforms had played a big role as a leverage, both during the pandemic and in the post-pandemic as has predicted and discussed in a two-way Focus Group Discussion methods (FGD), it taken from any webinars sessions involved the expert, officials, and the practitioners which concluded that instead of waiting a crisis assumed just taken place for a moment while waiting for the usual state return, it has been realized globally as an evidence as well as a signs that the new living ecosystem for orchestral musicians in Indonesia have just begun to change.